Exploring the impact of songs on student cognitive and emotional development - Dat Bao (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
This scholarly article investigates the impact of diverse songs on second language (L2) learning, emphasizing cognitive, kinesthetic, and emotional engagement. This research recognizes songs as literary expressions, specifically through the lens of lyrics as literary texts, and explores their historical and ongoing significance in L2 education. Beyond linguistic proficiency, the article delves into the broader implications of integrating songs into language education. Educators observe that incorporating music fosters a positive learning environment, contributing to increased motivation and engagement among learners. The discussion in this article addresses the gaps in the integration of literary texts, including songs, into language education. It criticizes the tendency of tertiary foreign language programs to overemphasize 'literature' at the expense of linguistic aspects and the opposite approach at the lower secondary level, which focuses on linguistic aspects while neglecting literary involvement. The results of this literature review highlight the need to recognize the profound impact that literary texts, including songs, have on individual learners, urging the incorporation of artistic elements into language teaching practices in a more comprehensive and balanced manner. This article emphasizes that literature, through stories and narratives, contributes to the emotional development of learners, fostering empathy and understanding of 'otherness.' This research advocates the balanced and thoughtful integration of literature in FL classrooms, recognizing its capacity to go beyond language instruction and contribute to broader education and individual growth.